2017
DOI: 10.5296/ber.v8i1.12135
|View full text |Cite
|
Sign up to set email alerts
|

Higher Education in Italy: Spatial Accessibility, Participation and Drop-outs

Abstract: Most previous research has focused on individual and family characteristics as predictors of high school leavers' behaviour towards higher education. However, far too little attention has been paid to the spatial dimension of the subject. This paper aims to narrow this gap by studying whether spatial accessibility of universities from parental residences influences the decisions of higher education participation and dropouts once enrolled to a university in Italy. First a modified version of Hansen gravity ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…The negative standardized coefficient of 0.003 indicated that student retention rate appeared to decrease as a university was located further away from the nearest metropolitan area. Even though this spatial variable was never explored prior to this research, these estimates were congruent with the findings of similar studies that examined the geographic discrepancies in education [43,45].…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The negative standardized coefficient of 0.003 indicated that student retention rate appeared to decrease as a university was located further away from the nearest metropolitan area. Even though this spatial variable was never explored prior to this research, these estimates were congruent with the findings of similar studies that examined the geographic discrepancies in education [43,45].…”
Section: Resultssupporting
confidence: 83%
“…There have been a few attempts to explore the importance of place for students and institutions, though not much attention was given to retention. According to Turk [43], spatial accessibility measures could be used as strong predictors of student behavior and success. Franklin [44] and Kim et al [45] indicated that geographic-spatial factors could influence student choices, academic performance, and student persistence.…”
Section: Spatial-demographic Factorsmentioning
confidence: 99%